2011
DOI: 10.1093/cvr/cvr147
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of ACE and mast cell chymase to endogenous angiotensin II generation and leucocyte recruitment in vivo

Abstract: In vivo, Ang II is primarily generated by ACE under basal conditions, but in inflammatory conditions, the release of MCP amplifies local Ang II concentrations and the associated inflammatory process. Thus, AT(1) receptor antagonists may be more effective than ACE inhibitors for treating ongoing Ang II-mediated vascular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…In addition to renin, angiotensin-II is produced as a result of release of mast cell chymase and this mechanism may be more important than the renin-angiotensin system in the generation of angiotensin following mast cell activation. 63 …”
Section: Mediators Released and Generated By Mast Cellsmentioning
confidence: 99%
“…In addition to renin, angiotensin-II is produced as a result of release of mast cell chymase and this mechanism may be more important than the renin-angiotensin system in the generation of angiotensin following mast cell activation. 63 …”
Section: Mediators Released and Generated By Mast Cellsmentioning
confidence: 99%
“…21 Mice were anesthetized by intraperitoneal injection with a mixture of xylazine hydrochloride (10 mg/kg) and ketamine hydrochloride (200 mg/kg), and 100 μL of vehicle or 0.1 μmol/L Ang-II was injected intrascrotally. Responses were determined 24 hours later.…”
Section: Intravital Microscopymentioning
confidence: 99%
“…There are some methods to modulate MCs. A MC stabilizer, cromolyn (CRM), and a MC degranulator, compound 48/80 (CMP 48/80; chemical formula of the monomer: C11H15NO), have previously been used to study MC function in vivo [7,15]. We demonstrated that CRM can stabilize hepatic MCs to prevent degranulation and that CMP 48/80 can deplete hepatic MCs through degranulating most of the stored granules by repeated injections [16] (data not shown).…”
mentioning
confidence: 89%